Strategy for Developing Lecturers' Integrity and Competence Through the WCU Model to Meet International Standards - Abubakar Ditruna; Sumarto Sumarto; Asep Suryana; Eka Surachman (STAI Hubbulwathan Duri, 2023)
The objective of this study was to establish a lecturer development model that enhances the global competitiveness of higher education by focusing on integrity and competence, in accordance with international norms. This study employed a hybrid methodology, consisting of two distinct stages: quantitative and qualitative. The structural equation modelling (SEM) analysis reveals that the direct relationship between integrity and competence is 0.458. Furthermore, the impact of integrity on performance is 0.446, while the effect of competence on performance is 0.460. It can be inferred that everything is in a state of moderation. One of the aspects that affects the worldwide competitiveness of higher education is the calibre of instructors. Proficient instructors possess exceptional honesty and expertise, enabling them to generate superior scientific works that are pertinent to societal demands. An important criterion for assessing the proficiency of a lecturer is their aptitude for publishing scholarly research in esteemed international publications, particularly those that are accredited by Scopus. Utilising Scopus publications can enhance the integrity and competence of teachers. The integrity of a lecturer can be assessed based on the calibre of their scientific output, whereas the competency of a lecturer can be evaluated by the extent to which their scientific work aligns with worldwide norms.